The Effect of the mission transfer from Chaloem Phrakiat 60th Anniversary Nawaminthrachini Health Station and Subdistrict Health Promoting Hospital to provincial administrative organization in Thailand. - Soontaraviratana, Boonma (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2026)
This mixed-methods study aimed to examine the impacts on the public and health personnel resulting from the transfer of responsibilities for the Chalermphrakiat 60th Anniversary Her Majesty the Queen’s Health Stations and Subdistrict Health Promoting Hospitals to Provincial Administrative Organizations in Thailand. The study was conducted between July and September 2023. Data were analyzed using descriptive statistics and content analysis. The findings were: (1) Among service users, no quantitative differences were found in health services before and after the transfer across all measured items; however, qualitative data reflected a decline in some primary care services, such as chronic disease clinics and dental services. (2) For health personnel, the overall impact score was 3.65/5 (SD = 0.655). The mean satisfaction relative to personnel expectations was 3.44/5 (SD = 0.651). Qualitative findings indicated that drivers of the transfer included low morale regarding career advancement and budgeting processes that require routing through contracted main service units, which posed significant obstacles. Initial impacts included an imbalance between the number of staff and the transferred service units, and barriers arising from laws, regulations, rules, and memorandum of cooperation agreements. Preparedness prior to transfer specifically clear regulations, procedures, memoranda of cooperation, and ensuring a balance between the number of transferred service units and the number of transferred health personnel is necessary to mitigate negative impacts on both service providers and service recipients.